Forecasting crude palm oil prices : statistical versus artificial inteligence approaches / Abdul Aziz Karia - Karia, Abdul Aziz (Institute of Graduate Studies, UiTM, 2014)
An accurate prediction of crude palm oil (CPO) prices is important especially when investors deal with ever-increasing risks and uncertainties of the businesses in future. Observation on the movement of CPO prices suggests an inconsistent trend as the CPO prices fluctuate from time to time. With regard to this, there is need for a development of an accurate model CPO prices prediction to facilitate efficient decision making from investors, businesses and policy makers. This prediction will at least provide a time lag between the decision making and the time at which the situation reaches the market place. Therefore, the main objective of this study is to determine the most appropriate model for the prediction of CPO prices in Malaysia.